A miniaturized readout strategy for endogenous histone deacetylase activity1. Issue 7 (16th July 2015) - Jost, Jan Oliver; Hanswillemenke, Alfred; Schwarzer, Dirk
<x xml:space="preserve">Abstract</x> Histone deacetylases are important drug targets, which are difficult to characterize due to their poor accessibility.